IMPLEMENTASI NORMA KESOPANAN PADA PERILAKU PESERTA DIDIK KELAS X IPA SMA NEGERI 10 PONTIANAK - Novita Suryani; Purwanti Purwanti; Yuline Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Abstract .This study aims to describe the implementation of politeness norms in the behavior of class X science students. The indicators studied were: norms of politeness in associating with parents; norms of politeness in associating with teachers; norms of politeness in associating with older people; norms of politeness in associating with younger people; norms of politeness in associating with peers; and norms of politeness in getting along with the opposite sex. This study uses a quantitative approach in the form of survey research. The data collection instrument in this study was a questionnaire. The results showed that the implementation of politeness norms on the behavior of students in class X science was in the good category with a percentage of 76.68%. The application of politeness norms in the behavior of class X science students is in the form of being polite to parents and younger people, respecting and appreciating teachers, older people, and the opposite sex, as well as being considerate and loyal to friends. Suggestions for Guidance Counseling teachers need to provide classical services about the importance of respecting and being democratic with younger people.Keywords: Parents, Peers, Politeness Norms, Teachers, the Opposite Sex